Behaviour of Cr in runoff from two catchments underlain by felsic bedrock. Issue 16 (9th December 2020) - Andronikov, A. V.; Novak, M.; Kram, P.; Sebek, O.; Andronikova, I. E.; Efremenko, N. A.; Borodulina, G. S.; Subetto, D. A.; Stepanova, M.; Antalova, E.; Levichev, M. A.; Zobkova, M. V.; et al.
ABSTRACT: Chromium isotope and chemical compositions in runoff from two felsic rock catchments, the Lysina (LYS; Czech Republic) and the Neglinka (NEG; northwest Russia), were studied. Three types of water were identified: Na-Ca-SO4 type for the LYS, Mg-Ca-Cl-HCO3 type for the NEG downstream, and Mg-Ca-Cl to Mg-Ca-HCO3 type for the NEG upstream. The Cr (III) liberated during soil/bedrock weathering oxidized to Cr (VI), which was the main dissolved Cr species in both catchments. Variations in δ 53 Cr values for LYS runoff (–0.07‰ to +0.37‰) reflected a sole Cr source, seasonality of weathering and hydrologically controlled leaching/export processes. In the NEG catchment, back-reduction of Cr (VI) to Cr (III) during riverine transport resulted in a decrease in Cr concentrations (to 10–30%) and in an increase of δ 53 Cr values (+0.09 to +0.42‰ for the upstream to +0.72 to +1.73‰ for the downstream). Groundwater discharge could have influenced the chemical composition of the downstream NEG runoff to some extent.